Komunikasi Kelompok Eating Reorder dalam Membangun Supportivitas - Sharka, Yoliandra Nur; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This research aims to investigate how group communication occurs in a healthy living program to build supportiveness. The researcher conducted a study on Eating Reorder, specifically In the WhatsApp group Batch 6 – Coach Chili. The research methodology employed a descriptive qualitative approach with a case study method. Data collection techniques included participatory observation and interviews. The theoretical framework used by the author consists of group commucination theory and supportiveness. The results of this research led the author to conclude that the dynamics of group communication appear less active, but it does not diminish the supportiveness within the group. The existence of the group significantly aids members in participating in the Eating Reorder program. There are rules that members need tp adhere to, and the function of group communication within this group is to solve problems. Additionally, the are three forms of supportive education within the group: Teaching, Guiding, and Supporting. Penelitian ini bertujuan untuk mengetahui bagaimana komunikasi kelompok yang terjadi pada sebuah program hidup sehat dalam membangun supportivitas. Penulis mengambil studi pada Eating Reorder khususnya pada grup WhatsApp Batch 6 – Coach Chili. Metodologi penelitian yang digunakan adalah pada pendekatan deskriptif kualitatif dengan metode studi kasus. Teknik pengumpulan data observasi partisipatif dan wawancara. Teori yang penulis gunakan adalah teori komunikasi kelompok dan supportivitas. Hasil dari penelitian ini, penulis dapat menarik kesimpulan dinamika komunikasi kelompok yang terjadi terlihat kurang aktif akan tetapi tidak mengurangi supportivitas di dalam grup. Adanya grup tersebut sangat membantu member-member dalam menjadi program Eating Reorder tersebut. Terdapat aturan-aturan yang perlu ditaati oleh member, fungsi dari komunikasi kelompok di dalam grup ini adalah sebagai pemecah masalah, dan terdapat 3 bentuk supportive educative di dalam grup tersebut yakni, Pengajaran (Teaching), Bimbingan (Guiding), dan Dukungan (Supporting).